Trends in prevalence of pre-existing diabetes and perinatal outcomes: a large, population-based study in Catalonia, Spain, 2006–2015. Issue 1 (26th October 2020) - Gortazar, Lucia; Goday, Albert; Flores-Le Roux, Juana Antonia; Sarsanedas, Eugènia; Payà, Antonio; Mañé, Laura; Pedro-Botet, Juan; Benaiges, David
Abstract : Introduction: This study aims to assess trends in the prevalence of pre-existing diabetes and whether the risk of adverse perinatal outcomes decreased in women between 2006 and 2015 in Catalonia, Spain. Research design and methods: A population-based study of 743 762 singleton deliveries between 2006 and 2015 in Catalonia, Spain, was conducted using data from the Spanish Minimum Basic Data Set. Cases of type 1 diabetes (T1DM) and 'type 2 diabetes and other pre-existing diabetes' ('T2DM and other PGD') were identified using International Classification of Diseases, Ninth Revision, Clinical Modification codes. Crude and age-adjusted annual prevalences were calculated. Poisson regression model was used to assess trends in prevalence and perinatal outcomes during the study period. Results: Overall prevalences of pre-existing diabetes, T1DM and 'T2DM and other PGD' were 0.52% (95% CI 0.51 to 0.54), 0.17% (95% CI 0.17 to 0.18) and 0.35% (95% CI 0.33 to 0.36), respectively. From 2006 to 2015, rates increased for pre-existing diabetes (from 0.43 (95% CI 0.39 to 0.48) to 0.56% (0.50 to 0.62), p<0.001), T1DM (from 0.14 (0.11 to 0.17) to 0.20% (0.17 to 0.23), p<0.001) and 'T2DM and other PGD' (from 0.29 (0.25 to 0.33) to 0.36% (0.31 to 0.40), p<0.001). Pre-eclampsia rose in women with pre-existing diabetes (from 4.38% to 8.97%, adjusted p<0.001), T1DM (from 3.85% to 12.88%, p=0.005) and 'T2DM and other PGD' (from 4.63% to 6.78%, adjusted p=0.01). Prevalence of prematurity, cesarean section and small for gestational age remained stable in all diabetes groups. However, the prevalence of macrosomia fell in women with pre-existing diabetes (from 18.18% to 11.9%, adjusted p=0.011) and 'T2DM and other PGD' (from 14.71% to 11.06%, non-adjusted p=0.022, adjusted p=0.305) and large for gestational age decreased in all diabetes groups (from 39.73% to 30.25% in pre-existing diabetes, adjusted p=0.004). Conclusions: The prevalence of pre-existing diabetes increased significantly in Catalonia between 2006 and 2015. Despite improvements in outcomes related to excessive birth weight, pre-eclampsia rates are rising and overall perinatal outcomes in women with pre-existing diabetes continue to be markedly worse than in the population without diabetes.